New records of polychaetes (Annelida: Polychaeta) from three locations of Oaxaca, Mexico - Chávez-López, Yessica (2019)
Introduction: The knowledge of polychaetes from Oaxaca, Mexico, is represented by 41 families and 241 species, nevertheless, 148 species are considered questionable. The majority of taxonomic studies of polychaetes in Oaxaca have taken placed on estuarine zones or commercial ports, sidelining other marine ecosystems. Objective: To identify the polychaeta-fauna from three different marine ecosystems in Oaxaca, Mexico. Methods: Specimens analyzed came from the Sección de poliquetos de la Colección Científica at the Laboratorio de Sistemática de Invertebrados Marinos, Universidad del Mar. The material deposited in the collection was collected between 2007-2017; additionally, new collect were realized in 2017. For each locality, the family and species richness were estimated using the accumulation function of linear dependence model. Results: One hundred lots and 273 specimens were revised. Seventy-one taxa, belonging to 47 genera and 21 families were identified, only twenty of these taxa are confirmed species (28 %). Chacahua Lagoon had the highest richness and relative abundance with 37 taxa and 149 specimens, Agua Blanca was identified 21 taxa and 92 specimens, and from San Agustín 19 taxa and 32 specimens. Sabellariidae had the highest relative abundance (58 specimens), while Phyllodocidae presented the highest species richness (12 species). Conclusions: This study adds 75 new records of taxa of polychaetes to the coast Oaxaca, which increase the knowledge in this animal group, now represented by 304 species, belonging to 154 genera and 42 families.